The effect of haemoglobin and blood transfusion on preterm infant gut perfusion and injury - Claire Howarth; Christian Mifsud; Christian Mifsud; Jayanta Banerjee; Simon Eaton; Terence Leung; Paul Fleming; Joan Morris; Narendra Aladangady (Frontiers in Pediatrics)
IntroductionThere is significant uncertainty regarding the role that anaemia or red blood cell transfusion (RBCT) plays in the development of gut injury in preterm infants. This study evaluated Near Infrared Spectroscopy (NIRS) together with a range of known biomarkers of gut inflammation to identify their relationship with anaemia and RBCT.MethodA prospective observational study of preterm infants born at <30 weeks gestation was conducted from birth until either 36 weeks post conceptional age or discharge home. Gut perfusion and biomarkers of gut injury were assessed weekly by: 60 min NIRS measurements (splanchnic tissue oxygenation index [sTOI] and fractional tissue oxygenation extraction [sFTOE]); stool calprotectin; urine intestinal and liver fatty acid binding proteins (I-FABPs and L-FABPs); and trefoil factor 3 (TFF-3). Exclusion criteria included Fetal Growth Restriction (FGR), and abnormal antenatal Dopplers. Haemoglobin (Hb) levels were measured in parallel with NIRS measurements. NIRS, together with urine and stool biomarkers of gut injury, were evaluated up to 72 h pre/post RBCT and pre/post measurements compared.ResultsForty-eight infants were studied. Median (range) gestational age was 26 + 3 (23 + 0 to 29 + 6) weeks and birthweight 883.5 g (460–1,600). Seven (14.6%) infants developed ≥ Bells stage 2 NEC. 28 (58.3%), 5 (10.4%) and 24 (50%) infants had ECHO confirmed PDA, haemorrhagic parenchymal infarct (HPI) and IVH respectively. There were 22 episodes of sepsis. Infants were in the study for a median of 7.3 (1–13) weeks. There was no significant association between Hb divided into three categories (<80 g/L, 80–111.9 g/L and ≥120 g/L) or continuous values and sTOI, sFTOE or any of the gut injury biomarkers measured (p > 0.05). 283 RBCTs were administered; 117 (41.3%) within the first two weeks of life. Pre and post blood transfusion changes in splanchnic NIRS oxygenation, urine and stool gut injury biomarkers were measured in 165, 195 and 175 episodes of RBCT respectively. There was no significant post RBCT changes in splanchnic NIRS or gut injury biomarker levels (p > 0.05). However, post RBCT calprotectin was significantly reduced during the first 14 days of life (mean difference −114%, CI −185 to −42 & p 0.002).ConclusionThere was no association between anaemia or RBCT with NIRS measurements of tissue oxygen saturation and biomarkers of intestinal inflammation or gut injury in preterm infants enrolled in this study. Further studies with standardised methods of examining the relationship between anaemia, RBCT and gut injury are needed.